(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Dai cittadini alle persone: la rivoluzione dell’ospitalità del diritto - 2. Le democrazie costituzionali e l’UE: il progetto di una sovranità ospitale - 3. L’ospite nel diritto cosmopolita: i confini del diritto di ospitalità - 4. Dall’ospitalità alla cittadinanza plurale: l’ospite musulmano e il diritto di libertà religiosa come ospitalità. The hospitality of the right or the arduous journey of human dignity ABSTRACT: The paper, starting from the idea of law as a producer and, at the same time, an expression of the hospitality of a political community investigates the progressive opening of state legal systems to the "stranger" in the age following the Universal Declaration of Human Rights. The paper highlights the difficulty in the implementation of an effective multi-level protection of fundamental rights and the resilience of the ancient paradigms of Westphalian sovereignty. In conclusion, the role of the right to religious freedom is underlined as the right to hospitality for the stable construction of multicultural and multireligious societies.